Odpowiedzi

Najlepsza Odpowiedź!
2010-03-29T17:10:03+02:00
A) 0,7x+1 1/5 = 4,(1-1 2/5x) +3
0,7x +1,2 = 4,5 (1 - 1,4x)+3
0,7x +1,2 = 4,5 - 6,3x 3
0,7x +6,3x= 4,5+3 - 1,2
7x=6,3/:7
x = 0,9
b)4/(4,5x-6) = -2(2/5x +1) +6 +4,4x
0,8(4,5x-6) = _2(0,4x +1) +6 4,4x
3,6x - 4,8 = -0,8 - 2 +6 +4,4x
3,6x +0,8x - 4,4x = 4,8 - 2 6
0 = 8,6
równanie sprzeczne
c)2y + 2/5(-1,2y -1) - 18/25y = 4(0,32y - 0,22)
2y + 0,4(-1,2-1) - 0,72y = 1,28y - 0,88
2y - 0,48y - 0,4 - 0,72y = 1,28y - 0,88
2y - 0,48y - 0,72y - 1,28y = -0,88 +0,4
-0,48y = -0,48/:(-0,48)
y = 1
d)0,8 - 1/5(0,3y-1) = 1/25(y+25) +0,02y
0,8 -0,2(0,3y - 1) = 0,04(y+25)+0,02y
0,8-0,06y+0,2=0,04y+1+0,02y
-0,06y-0,04y-0,02y=-0,8-0,2+1
-0,12y=0
y=0
Mam nadzieje ze nie popełnilam bledu